Evaluation of Gingival Microleakage in Class II Composite Restorations with Different Lining Techniques: An In Vitro Study - Vedavathi Bore Gowda; B. V. Sreenivasa Murthy; Swaroop Hegde; Swapna Devarasanahalli Venkataramanaswamy; Veena Suresh Pai; Rashmi Krishna (Scientifica)
Aim. To compare the microleakage in class II composite restorations without a liner/with resin modified glass ionomer and flowable composite liner. Method. Forty standardized MO cavities were prepared on human permanent mandibular molars extracted for periodontal reasons and then divided into 4 groups of ten specimens. The cavity preparations were etched, rinsed, blot dried, and light cured and Adper Single Bond 2 is applied. Group 1 is restored with Filtek P60 packable composite in 2 mm oblique increments. Group 2 is precure group where 1 mm Filtek Z350 flowable liner is applied and light cured for 20 sec. Group 3 is the same as Group 2, but the liner was cocured with packable composite. In Group 4, 1 mm RMGIC, Fuji Lining LC is applied and cured for 20 sec. All the teeth were restored as in Group 1. The specimens were coated with nail varnish leaving 1 mm around the restoration, subjected to thermocycling, basic fuchsin dye penetration, sectioned mesiodistally, and observed under a stereomicroscope. Results. The mean leakage scores of the individual study groups were Group 1 (33.40), Group 2 (7.85), Group 3 (16.40), and Group 4 (24.35). Group 1 without a liner showed maximum leakage. Flowable composite liner precured was the best.